Cover Picture: Ylide‐Functionalized Phosphines: Strong Donor Ligands for Homogeneous Catalysis (Angew. Chem. Int. Ed. 39/2018). Issue 39 (20th August 2018) - Scherpf, Thorsten; Schwarz, Christopher; Scharf, Lennart T.; Zur, Jana‐Alina; Helbig, Andreas; Gessner, Viktoria H.
Abstract : Power to phosphines Phosphines are one of the most utilized types of ligands in catalysis and their advancement is indispensable for further developments in this field. In their Communication on page 12859 ff., V. H. Gessner et al. demonstrate that ylide functionalization is a powerful tool to increase the donor strength of phosphines. The YPhos ligands obtained are easy to synthesize, more electron‐rich than classical phosphines or even NHCs, and allow for improved catalytic activity in gold catalysis.